Mainstreaming Energy Efficiency Investments in Urban Water and Wastewater Utilities - Limaye, Dilip (World Bank, Washington, DC, 2019)
This guidance note presents an overview of the benefits of improving energy efficiency in urban water and wastewater utilities (WWUs). It defines the typical energy efficiency and load management measures and the process to identify and assess these measures. The note addresses some of the major considerations related to implementation and financing of investments in energy efficiency, and highlights past activities and lessons learned. Included are suggested actions by national and local governments, international financial institutions, and senior management of WWUs for promoting energy efficiency in WWUs, and a road map for mainstreaming energy efficiency in water sector infrastructure projects.